Fatty acid alkyl ester nanowebs suitable for renewable thermal energy storage - Önder Karaoğlu, Emel; SARIER, NİHAL (My University, 2020)
Owing to their high heat absorption and release capacities, chemical and thermal stability, non-toxicity, two fatty acid alkyl esters (FAAEs), methyl palmitate (MP) and isopropyl palmitate (IPP), were investigated for their use as thermal energy storage (TES) material in a shape stabilized form. Four nanowebs were developed via coaxial electrospinning, using poly(acrylo nitrile) (PAN) or poly(methacrylic acid-co-ethyl acrylate) (PMEA) shell to envelope MP or IPP core. Scanning electron microscope (SEM), transmission electron microscope (TEM) images confirmed cylindrical nanofiber formation, demonstrating a coaxial sheath-core morphology. The phase change enthalpies of PAN-MP, PMEA-MP nanowebs, with average diameters of 259–289 nm, were 71 J g−1 and 86 J g−1 at 28–32 °C, and those of PAN-IPP, PMAE-IPP were 72 J g−1 and 60 J g−1 at 7–15 °C during heating cycle in differential scanning calorimeter (DSC) analyses. A composite including PAN-MP nanoweb performed enhanced thermo-physical properties than its control counterpart.
Keywords: Coaxial Electrospinning; DSC; Fatty Acid Alkyl Esters; Nanowebs; Phase Change Material; Thermal